A STUDY OF IRAQI SECONDARY STUDENTS' ATTITUDES TOWARD PEER FEEDBACK - Ameen, Badr Jaafar; Ali AL-Zurfi (Academic Journal Research, 2025)
Objective: This study aimed to explore the attitudes of Iraqi high school students toward peer feedback in English as a Foreign Language (EFL) classrooms. Method: Using a quantitative research design, this study surveyed 59 male high school students in Najaf City, Iraq, to understand their perceptions of peer feedback. Results: The results indicate that students generally have positive attitudes toward peer feedback, finding it beneficial for improving their writing skills and motivating them to learn. However, students also expressed concerns about their ability to provide accurate feedback due to a lack of confidence in their grammatical knowledge. These findings suggest that while peer feedback is a useful tool in EFL classrooms, students may require additional training and support to fully benefit from it. Novelty: The study contributes to the broader discourse on feedback in education by highlighting the importance of cultural and contextual factors in implementing peer feedback practices.